DEIKSIS DALAM TEKS ANEKDOT KORAN KOMPAS EDISI APRIL SAMPAI JULI 2019 - Wa Ode Halfian; Rabiatul Adawiah; Fina Amalia Masri (Seshiski: Southeast Journal of Language and Literary Studies, 2022)
This research is motivated by the widespread appearance of anecdotal texts in the mass media, one of which is newspapers. This anecdote appears for various purposes and purposes. In order to understand the intent and purpose, the reader must be able to understand the meaning contained in the anecdote text. This research focused on anecdotal texts in the Kompas Newspaper in April to July 2019 editions. The problem in this research is questioning the types of deixis contained in anecdotal texts in the Kompas newspaper in April to July 2019 editions. Data collection techniques are online data retrieval techniques analyzed through a qualitative descriptive method. The study showed that the types of deixis contained in anecdotal texts in the April to July 2019 editions of Kompas Newspaper are covered; deixis of persona that consisted of the first persona deixis in the form of “I”, “I”, “we” and “we”, the second persona in the form of “you”, “you”, “you”, and “your bound form”, and the third persona of “he” and “they”. Deixis of space or place appears in the form of “this” and “here”, and the deixis of time is appeared in the form of “now”, “tomorrow”, and “then”.